Cyrtomium remotipinnum (Dryopteridaceae), a new species from karst area in Guangxi, China - Nong, Su-Yun; Liu, Yan; Yan, Ke-Jian; Wei, Hong-Jin (Phytotaxa, 2023)
Cyrtomium remotipinnum, a new species of Dryopteridaceae from the karst areas in Guangxi, China, is described and illustrated. The new species is distinguished from the two most similar species, C. calcis and C. pachyphyllum, by its larger stature and higher length-to-width ratio of pinnae. The new species is classified as Critically Endangered (CR) following IUCN Red List Criteria. In addition, this study attempted to identify some easily confused Cyrtomium species by combining venation patterns and soral distributions with other characters.